Human system interaction with confident computing - Chang, Elizabeth; Dillon, Tharam S.; Calder, David (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This keynote will give an overview of the last 30 years of human system interaction and the key elements of Human Computer Interaction (HCI) and its transition from traditional HCI into the frontier of Human System Interaction (HSI). This leads to the discussion as to why HSI is about Digital Ecosystems and about the world we live in rather than just ICT. We explain the 5 Mega Trends, and the emergence of Confident Computing and how that is leading to the revolution of the next generation of Human System Interaction version 2.0 and Usability version 2.0. This is followed by the challenges and research issues within Human System Interaction (HSI).